Anti-migration Effect of Aaptos suberitoides Fraction in HCT-116 Colorectal Cancer Cell Line - Dany Muhammad Daffa; Muhammad Hasan Bashari; Eko Fuji Ariyanto; Tenny Putri; Nurul Qomarilla (Althea Medical Journal, 2021)
Background: Colorectal cancer is the second leading cause of mortality and the most prevalent cancer worldwide. Most patients, who come with late-stage, have ineffective treatments and some side effects in chemotherapy. Aaptos suberitoides has potential anti-cancer effects due to its bioactive compounds such as aptamine. This study aimed to evaluate the migration inhibition effect of Aaptos suberitoides fraction in HCT-116 cell line.Methods: This study was an experimental study. Aaptos suberitoides specimen was taken in Tinjil Island and fractionated with ethyl acetate. HCT-116 cell line was added with Aaptos suberitoides fraction and cellular migration activity was observed in 48 hours of which the scratch assay was performed. The gap closure area was determined with ImageJ software.Results: The data showed that a low concentration of Aaptos suberitoides fraction inhibited migration activity in HCT-116 cell line as follow; 1 and 5 mg/L Aaptos suberitoides fraction inhibit 3-4 % cancer cell migration in 24 hours, and 10-11% inhibition in 48 hours, respectively. However, 10 mg/L fraction concentration only inhibited 7-14% of the migration effect.Conclusion: Aaptos suberitoides fraction suggests insignificant migration inhibition in colorectal cancer cells and only inhibits less than 15 % HCT-116 cell line.